2020
DOI: 10.3892/ol.2020.12391
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA SNHG20 promotes ovarian cancer development by targeting microRNA‑338‑3p to regulate MCL1 expression

Abstract: Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs/miRs) were reported to be associated with the development of ovarian cancer (OC). Increasing evidence demonstrated that lncRNA SNHG20 and miR-338-3p were involved in OC. However, the functional mechanism of lncRNA SNHG20 and miR-338-3p in OC development remains unknown. The expression of SNHG20, miR-338-3p and myeloid cell leukemia 1 (MCL1) was detected by reverse transcription-quantitative PCR. MTT assay, flow cytometry and transwell migration and invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) are transcripts over 200 nucleotides in length and have no protein-coding potential [ 10 ]. The imbalance of lncRNAs is related to the proliferation, invasion and metastasis of cancer cells [ 11 ]. SNHG20 involves in many types of cancer, such as cervical cancer and liver cancer [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (lncRNAs) are transcripts over 200 nucleotides in length and have no protein-coding potential [ 10 ]. The imbalance of lncRNAs is related to the proliferation, invasion and metastasis of cancer cells [ 11 ]. SNHG20 involves in many types of cancer, such as cervical cancer and liver cancer [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs), ∼22 nucleotides, exert crucial roles via inhibiting translation or promoting degradation [ 11 ]. Multiple studies demonstrated that miRNAs participated in the progression of various cancer types, including non-small cell lung cancer [ 14 ], colorectal cancer [ 15 ], thyroid cancer [ 16 ] and esophageal cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%